O papel das organizações não-governamentais no acolhimento de crianças venezuelanas deslocadas no Brasil (2019-2020) - Façanha, Klebiane Queiroz (2023)
The intense flow of displaced Venezuelans in Brazil raises questions about the situation of displaced Venezuelan children, making it crucial to discuss their reception. This research has the general objective of understanding how they are welcomed in the scope of the Welcome Operation (WO). Particularly, it aims to identify which NGOs acts specifically in the reception of displaced Venezuelan children in the State of Roraima, list the practices they carried out within the scope of the WO for their reception, and reflect on whether they are in conformity with international and national children protection standards. Finally, it discusses the performance of these NGOs to understand the relevance of participating in the Welcome Operation from the perspective of International Cooperation. To achieve these aims, a qualitative bibliographical study was carried out. The results indicate that the reception of displaced Venezuelan children, within the scope of the WO, occurs through the provision of services and activities in the context of a humanitarian emergency, facilitated by cooperation agreements involving the Brazilian government, UNHCR, and UNICEF. The NGOs act as implementing partners of the actions and programs developed by the mentioned UN agencies in shelters of Boa Vista/RR and Paracaíma/RR. The prolonged stay of children in shelters stands out, evidencing the dilution of the emergency nature of reception actions. It is imperative to accelerate the process of recognition as a refugee, ensuring compliance with child protection standards established by international and national laws. In addition, it is important to emphasize the limitations of the WO regarding the capacity to meet the demands arising from the intense flow, highlighting the need to involve other actors to implement actions that are more efficient. This research can contribute for civil society formation, and for the elaboration of strategies that can consider the Venezuelan displaced child as an active subject. In addition, it can help to establish a research agenda on the subject in the field of International Relations to promote the debate.